The Effect of Realistic Mathematics Approach on Emotional Intelligence and Mathematical Communication Ability of Grade V Students - Andini, Putri; Hasratuddin; Kandaga, Thesa (Global Action and Education for Society, 2025)
This research method uses a quantitative approach and the type of research is a quasi-experiment. The research design used is a quasi-experiment with a 2 x 2 factorial with a 2-way analysis of variance (ANOVA) technique. This test validation sheet consists of three components, namely content, construction, and language use. The data analysis technique used in this study is the inferential statistical technique. Hypothesis testing in this study was carried out using the analysis of variance (ANOVA) test with a 2 x 3 test and a significance level of 0.05. Before the ANOVA test was carried out, the analysis requirements test was first carried out, namely the normality test and the data homogeneity test. This study is a quasi-experimental study by comparing the mathematical communication skills of students taught with a realistic mathematical approach compared to the mathematical communication skills of students taught with ordinary learning. In addition, this study also looks at the comparison of students' mathematical communication skills based on the level of emotional intelligence possessed by students, while the data on students' emotional intelligence was obtained through an emotional intelligence questionnaire given during the study.